"We are nurses – what can we say?": power asymmetries and Auxiliary Nurse Midwives in an Indian state. Issue 2 (1st January 2022) - Das, Priya; Ramani, Sudha; Newton-Lewis, Tom; Nagpal, Phalasha; Khalil, Karima; Gharai, Dipanwita; Das, Shamayita; Kammowanee, Rochana
Abstract: In India, nurses and midwives are key to the provision of public sexual and reproductive health services. Research on impediments to their performance has primarily focused on their individual capability and systemic resource constraints. Despite emerging evidence on gender-based discrimination and low professional acceptance faced by these cadres, little has been done to link these constraints to power asymmetries within the health system. We analysed data from an ethnography conducted in two primary healthcare facilities in an eastern state in India, using Veneklasen and Miller's expressions of power framework, to explore how power and gender asymmetries constrain performance and quality of care provided by Auxiliary Nurse Midwives (ANMs). We find that ANMs' low position within the official hierarchy allows managers and doctors to exercise "power over" them, severely curtailing their expression of all other forms of power. Disempowerment of ANMs occurs at multiple levels in interlinked and interdependent ways. Our findings contribute to the empirical evidence, advancing the understanding of gender as a structurally embedded dimension of power. We illustrate how the weak positioning of ANMs reflects their lack of representation in policymaking positions, a virtual absence of gender-sensitive policies, and ultimately organisational power structures embedded in patriarchy. By deepening the understanding of empowerment, the paper suggests implementable pathways to empower ANMs for improved performance. This requires addressing entrenched gender inequities through structural and organisational changes that realign power relations, facilitate more collaborative ways of exercising power, and create the antecedents to individual empowerment.